Earth (Journal of Parents and Teachers, 2014)
From activities before watching the film, from the analysis of many of its sequences and from activities of experience, reflection and action, the author has a bearing on values as respect and care of environment, sustainability and also responsibility and commitment facing diversity. The activities are related to issues as: the importance of biodiversity, earth as a unit of life, environmental effects of men action, climate change, the water and climate cycle and lastly the seasons.
Keywords: Environmental education; sustainability; biodiversity; cinema and transversal